Evaluation of Healthy Lifestyle Behaviours of faculty Members - Senbakar, Kubilay (Mattioli 1885, 2021)
The aim of this study is to evaluate the healthy lifestyle behaviours of the faculty members. Population of the research is consisted of the faculty members in Firat University in Elazig province. Its sample consisted of 150 faculty members randomly selected among the faculty members. In our study, the validity of the scale developed by Walker et al. (1987) and subsequently revised (1996), in Turkey was done by Bahar et al. (2008). Accordingly, sub-dimensions of SYBD (Healthy Lifestyle Behaviours) consisted of 52 questions and come under 6 dimensions are as follows: Spiritual development, health responsibility, physical activity, nutrition, interpersonal relationships, and stress management. All questions regarding SYBD are never calculated by likert scale such as never (1), sometimes (2), often (3), regularly (4). In the analysis of data in the study and the calculation of results obtained, SPSS 22,0 statistical program was used. The significance level was determined as P<0,05 in the analyses carried out. In the study we carried out, statistical significance was found in the sub-dimensions of health responsibility, physical activity, and stress management in the analysis of the sub-dimensions of the SYBD scale of the gender variable of the members according to the T test, in the analysis of the sub-dimensions of the SYBD scale of the marital status variable according to the T test, it was determined that there was statistical significance in the sub-dimensions of spiritual development and stress management (p <0.05). In Anova analysis of age, 36-40-year-old faculty members were determined as the group made difference. As a result, through this research, it was observed that the values were above average looking at the sub-dimensions of the evaluation of healthy lifestyle behaviours of Faculty Members. It was determined that the faculty members have healthy lifestyle behaviours.
Keywords: Faculty Member; Health; Healthy Lifestyle